Kebutuhan Media Belajar di Era COVID-19: Pengembangan Buku Ajar Mata Kuliah Model Pembelajaran dalam Pendidikan Jasmani - Setiawan, Edi; Jumareng, Hasanuddin; Kastrena, Ervan; Juliantine, Tite; Gani, Ruslan Abdul (Pusat Studi Ilmu Keolahragaan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2021)
The difficulties experienced by students in obtaining knowledge and studying material in physical education learning models in the COVID-19 era became the main problem in this study. This study aims to develop textbooks for learning model courses in physical education for Physical Education, Health and Recreation students at Suryakancana University. This research is a Research and Development model with Borg & Gall. The subjects in this study involved three experts, namely content, language and media material experts as well as PJKR students. Data collection techniques through questionnaires and data analysis are quantitative and qualitative. The results of this study indicate that textbooks in the subject of learning models in physical education after going through the validation process by three experts and trials in stages I and II have met the criteria with the valid category or are suitable for use by students in lectures. The implication is that textbooks for physical education learning models can be used in the learning process in the era of COVID-19.